A randomised double-blind placebo-controlled crossover trial of HUMira (adalimumab) for erosive hand OsteoaRthritis – the HUMOR trial. Issue 7 (July 2018) - Aitken, D.; Laslett, L.L.; Pan, F.; Haugen, I.K.; Otahal, P.; Bellamy, N.; Bird, P.; Jones, G.
Summary: Objective: To assess the efficacy of adalimumab in patients with erosive hand osteoarthritis (OA). Method: Patients >50 years old, meeting the American College of Rheumatology (ACR) criteria for hand OA, with pain >50 on 100 mm visual analogue scale (VAS), morning stiffness >30 min and ≥1 erosive joint on X-ray with synovitis present on magnetic resonance imaging (MRI) were included in a randomised double-blind placebo-controlled crossover trial. Patients were randomised to adalimumab (40 mg subcutaneous injections every other week) or identical placebo injections for 12 weeks followed by an 8-week washout and then crossed over treatment groups for another 12 weeks. The primary outcome was change in VAS hand pain over 12 weeks. Secondary outcomes included change in Australian/Canadian Hand OA Index (AUSCAN) pain, function and stiffness subscales from baseline to 4, 8 and 12 weeks, change in MRI-detected synovitis and bone marrow lesions (BMLs) from baseline to 12 weeks and change in VAS from baseline to 4 and 8 weeks. Results: We recruited 51 patients and 43 were randomised to either Group 1 ( N = 18, active then placebo) or Group 2 ( N = 25, placebo then active). At 12 weeks there was no difference between the groups on the primary outcome measure (mean decrease in VAS pain of 3.2 mm standard deviation (SD 16.7) for adalimumab vs 0.8 mm (SD 29.6) for placebo). The adjusted treatment effect was −0.7 mm (95% confidence interval (CI) −9.3 to 8.0), P = 0.87. No statistically significant differences were found for any secondary outcomes. Conclusion: Adalimumab did not show any effect on pain, synovitis or BMLs in patients with erosive hand OA with MRI-detected synovitis as compared to placebo after 12 weeks. Clinical trial registration number: ACTRN12612000791831 .